The quality of professional education in the context of today's challenges (the example of future railway transport specialists education) - Nataliia Malanyuk (Ukrainian Journal of Educational Studies and Information Technology, 2020)
The article reveals the essence of the definition of "quality of education". The essence of notion is analyzed, based on the conceptual foundations of professional education reform. The components of modern professional education are decentralization of management and funding; social partnership in the field of professional education and training and the labor market; quality of professional education. The system model of railway transport specialists education is built and substantiated.